2006
DOI: 10.1002/hyp.6337
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydrological feedbacks and linkages associated with land degradation: a case study from Mexico

Abstract: Abstract:Land degradation and desertification are major environmental problems of human societies in drylands of North and South America. Mexico is one of the most severely affected countries. An assessment of how both biophysical and socio-economic processes simultaneously affect, and are affected by, land degradation is recognized as one of the most important and challenging topics in the research on global change. Towards meeting this challenge, in June 2004 an interdisciplinary mix of scientists assembled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 26 publications
(25 reference statements)
0
28
0
1
Order By: Relevance
“…Despite recent advances toward developing a common theoretical framework for studying desertification and managing desertified areas (Huber-Sannwald et al 2006, Reynolds et al 2007b, important uncertainties about this key environmental problem remain, particularly regarding the extent of the area affected, the relative importance of its biophysical and socioeconomic drivers, and the temporal dynamics of desertified and desertificationprone areas (Herrmann and Hutchinson 2005, Veron et al 2006, Reynolds et al 2007a. In this direction, the establishment of long-term and rigorous monitoring programs is probably the most effective way to assess the status of natural resources and the evolution of desertification processes (Tongway and Hindley 2004, Herrick et al 2005, Reynolds et al 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances toward developing a common theoretical framework for studying desertification and managing desertified areas (Huber-Sannwald et al 2006, Reynolds et al 2007b, important uncertainties about this key environmental problem remain, particularly regarding the extent of the area affected, the relative importance of its biophysical and socioeconomic drivers, and the temporal dynamics of desertified and desertificationprone areas (Herrmann and Hutchinson 2005, Veron et al 2006, Reynolds et al 2007a. In this direction, the establishment of long-term and rigorous monitoring programs is probably the most effective way to assess the status of natural resources and the evolution of desertification processes (Tongway and Hindley 2004, Herrick et al 2005, Reynolds et al 2007a.…”
Section: Introductionmentioning
confidence: 99%
“…Anselme et al 2010), to very simple qualitative descriptions of the system based on a few stakeholder-indentified relationships and thresholds (e.g. Huber-Sannwald et al 2006). Such an approach offers a structured opportunity for deliberation over the nature of key system relationships, the criticality of system thresholds and the identification of system feedbacks and adaptive strategies (Fish et al 2010).…”
Section: The Virtues and Challenges Of Deliberative Environmental Assmentioning
confidence: 99%
“…By contrast, the decline of hydrological ecosystem interferes the balance of other ecosystems and negatively affects the human well-being. Huber Sannwald et al (2006) concluded that water scarcity and land degradation interacted with each other formed a vicious circle. Tisdell (2001) also stated that water scarcity affected the natural flow, thus IWRM needed to take water supply for natural flow into account.…”
Section: Negative Effect Of the Changes Of Regional Hydrological Ecosmentioning
confidence: 99%